The linkage between forests and household food security: Empirical evidence from Shinyanga Region, Tanzania - Matilda Stanslaus Ntiyakunze; Jesper Stage (Trees, Forests and People)
Many rural forest dependents are still poor and exposed to food insecurity. Hence, this paper aims to study the linkage between forests and household food security by analysing factors that determine participation in forest activities and by examining differences between participants and non-participants in respect of the food-security outcome. The study was conducted in rural areas of the Shinyanga Region in Tanzania using cross-sectional data on a sample of 303 rural households. Marginal effects predicted that distance to the forest concerned, illness or death of a household member, and off-farm activities determined participation in forest activities. Propensity score matching revealed that those who participated in forest activities were less food secure than non-participants with comparable characteristics were, which supports the contention that rural forest dependents are prone to food insecurity. Government policy should, therefore, aim at enhancing alternative sources of income as well as food storage facilities and food production for rural households.